Taxonomic revision of Saudi Arabian Tetraena Maxim. and Zygophyllum L. (Zygophyllaceae) with one new variety and four new combinations (Bangladesh Journal of Plant Taxonomy, 2018)
The genera Tetraena Maxim. and Zygophyllum L. (Zygophyllaceae) present different morphological characters, viz. growth habit, leaf features, flower traits and fruit shape, and have a high diversity of species in Africa, Australia and Asia. Six species of Tetraena [T. alba (L.f.) Beier & Thulin, T. coccinea (L) Beier & Thulin, T. decumbens (Delile) Beier & Thulin, T. hamiensis (Schwein f.) Beier & Thulin, T. propinqua (Decne.) Ghaz. & Osborne and T. simplex (L.) Beier & Thulin], and one species of Zygophyllum (Z. fabago L.) have been identified in Saudi Arabia, most of which grow in sandy soils and saline habitats as shrubs and herbs. One new endemic variety (T. alba var. arabica Alzahrani & Albokhari) along with four new combinations [T. alba var. amblyocarpa (Baker) Alzahrani & Albokhari, T. hamiensis var. qatarensis (Hadidi ex Beier & Thulin) Alzahrani & Albokhari, T. hamiensis var. mandavillei (Hadidi ex Beier & Thulin) Alzahrnai & Albokhari, and T. propinqua subsp. migahidii (Hadidi ex Beier & Thulin) Alzahrani & Albokhari] are proposed. Descriptions, illustrations, distribution maps and a key for identification of the taxa are presented. Conservation status has been proposed for the new variety and combinations.Bangladesh J. Plant Taxon. 25(1): 19-43, 2018 (June)